SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP AS AN EFFECTIVE MEANS OF PROVIDING EMPLOYMENT FOR THE POPULATION - Kasimova Saida Muminovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article talks about the role and importance of small businesses and private business entities in ensuring the employment of the population, as well as the measures that should be taken to increase the level of employment.